The analysis of the settlement of the various types of geodetic benchmarks - Borowski, Łukasz; Lal, Agnieszka; Nepelski, Krzysztof (Budownictwo i Architektura / Civil and Architectural Engineering, 2017)
The paper presents the studies of the possible causes of the excessive settlement of geodetic benchmarks. For the purpose of the study, two types of ground benchmarks (type 75a and b) were selected. The computational analysis was carried out on benchmarks situated in different soil conditions and under two variants of load. The parameters were modified in order to reach the interaction between the subsoil and the structure, which is the closest to the actual conditions. Obtained results were compared with the settlement noted in Kętrzyn district, during heights frame transformation from Kronsztadt’60 to Kronsztadt’86. As a result, possible change of heights of geodetic points between land surveying campaigns (circa 20 years) could be estimated.